Media Development of Runner Mathematics Educational Game Based on Website Using Unity on Simple Fraction Material 5th Grade Elementary School - Azizah, Hanifah Nur; Abdullah, Kusmajid (Department of Mathematics Education Program IPI Garut, 2025)
Rendahnya minat dan hasil belajar siswa pada materi pecahan sederhana di kelas 5 SD menjadi dasar pengembangan media pembelajaran yang inovatif. Penelitian ini bertujuan untuk mengembangkan game edukasi Runner Mathematics berbasis website menggunakan Unity dengan model ADDIE. Data dikumpulkan melalui observasi, angket validasi ahli, dan angket respon siswa, kemudian dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa media ini layak digunakan dan mampu meningkatkan motivasi dan keterlibatan siswa. Game ini berpotensi menjadi media pembelajaran matematika yang interaktif dan mudah diakses. The low interest and learning outcomes of students in 5th-grade elementary school regarding simple fractions are the basis for the development of innovative learning media. This research aims to develop a website-based Runner Mathematics educational game using Unity with the ADDIE model. Data were collected through observation, an expert validation questionnaire, and a student response questionnaire, and then analysedanalysed both descriptively and quantitatively. The results show that this media is feasible to use and can increase student motivation and engagement. This game has the potential to be an engaging and accessible medium for learning math.